The Ethan I was before - Standish, Ali (Harper, 2019)
After an accident takes his best friend and his family moves from Boston to Palm Knot, Georgia, Ethan must figure out who he is and who he wants to be. Meeting Coralee, a girl with a large personality, may just be what Ethan needs, but can he help Coralee when she needs him the most.